Gaya kognitif dan penguasaan kemahiran saintifik dalam kalangan pelajar Fizik bagi tajuk daya dan gerakan - Ibrahim, Hafzan (2010)
Teaching methods should edify towards students’ cognitive aspects in mastering scientific skills. The purpose of this research is to determine the relationship between cognitive styles (CS) and scientific skill (SS) among form four physics students in the topic of Forces and Motion. Two types of cognitive styles had been focused in the research namely Field Independent (FI) and Field Dependent (FD). The study involved 216 respondents that consists of form four students from Alor Gajah district, Malacca who are taking physics subject in Pure Science stream. Two sets of test set had been handed out to the respondents which were the Ujian Kumpulan Bentuk-bentuk Terpendam (UKBT) and Ujian Kemahiran Saintifik Dalam Daya (UKSD). UKBT contains 24 complex figure and respondents were required to find a simple diagram in every complex figure. UKSD consists of 26 subjective questions on forces and motion that were constructed based on Curriculum Spesifications Physics Form Four, Integrated Curriculum for Secondary Schools (CDC, 2006). Time allocated was 80 minutes. The reliability and validity of UKBT was established at 0.82 and for UKSD is 0.83. To analyse the findings, descriptive statistics and inferential statistics were invoked. After analyzing, it was found that 86 respondents were FI while 68 respondents were FD. The remaining of 62 respondents were at the intermediate cognitive style. Besides that, FI samples are noted to have better control over their SS compared to FD respondents. However CS is not depend on SS. Moreover, FI respondents also have the ability in solving conceptual and analyse question compared to FD respondents. Despite that, FD respondent was better in generalizing information than FI respondents. Two independent variables were chosen and they were school’s location and gender. Study findings show that there are no significant relationships between cognitive styles with school’s location and sc gender. On the other hand SS was no significant relationships with gender but it correlate with the school’s location